The Effect of Transparency, Participation and Internal Control System on The Accountability of Village Fund Management - Sari, Dewi Wulan; Santosa, R. Ery Wibowo Agung; Nurcahyono, Nurcahyono (Economics and Business International Conference Proceeding, 2024)
This study aims to determine the transparency, participation and internal control system on the accountability of village fund management. The population in this study is village officials in Ngampel and Gemuh Districts who occupy the positions of village heads, village secretaries, village treasurers, and village government bodies. The data in this study is in the form of primary data with sampling using survey techniques. The data analysis method used in this study uses inferential statistical analysis and is measured using WarpPLS software. The results of the analysis show that transparency, participation and internal control system have a positive effect on the accountability of village fund management.